2022
DOI: 10.1186/s12989-022-00452-3
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled diesel exhaust particles result in microbiome-related systemic inflammation and altered cardiovascular disease biomarkers in C57Bl/6 male mice

Abstract: Background The gut microbiota plays a vital role in host homeostasis and is associated with inflammation and cardiovascular disease (CVD) risk. Exposure to particulate matter (PM) is a known mediator of inflammation and CVD and is reported to promote dysbiosis and decreased intestinal integrity. However, the role of inhaled traffic-generated PM on the gut microbiome and its corresponding systemic effects are not well-characterized. Thus, we investigated the hypothesis that exposure to inhaled d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 95 publications
3
7
0
Order By: Relevance
“…Thus, we propose that the HF diet is likely contributing to the increased baseline expression of TNF-α in the intestines of the CON group in this study. Moreover, we suggest that the reduction in TNF-α with DEP exposure is correlated to the observed expansion in Escherichia, which we previously reported [37]. When comparing PRO + CON to CON, we find a significant reduction in TNF-α expression, which we attribute to the known anti-inflammatory effects of probiotics, namely Lactococcus and Lactobacillus strains [65,66].…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Thus, we propose that the HF diet is likely contributing to the increased baseline expression of TNF-α in the intestines of the CON group in this study. Moreover, we suggest that the reduction in TNF-α with DEP exposure is correlated to the observed expansion in Escherichia, which we previously reported [37]. When comparing PRO + CON to CON, we find a significant reduction in TNF-α expression, which we attribute to the known anti-inflammatory effects of probiotics, namely Lactococcus and Lactobacillus strains [65,66].…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, we observe a significant increase in TNF-α with DEP + PRO compared to its respective CON + PRO control, suggesting that the immunomodulatory effects of probiotics normalized the immune response in the intestines which resulted in an augmented response with DEP exposure. We have previously reported that probiotic treatment mitigates the expansion of Escherichia observed with DEP exposure in the HF diet mice, confirming the possible role of Escherichia in TNF-α signaling in these mice [37].…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations